Kadar Glutation Pasca Pemberian Provitamin B5 pada Mencit BALB/c Terinfeksi Plasmodium berghei - Ekawanti, Ardiana (Jurnal Kedokteran, 2012)
Introduction: Malaria was one of the health problem in developing country including Indonesia. Three hundred to five hundred million people suffered from malaria, and causing more than one million death annually. The objective of this study was to find out erythrocyte GSH level and compared to parasitemiapercentage due to provitamin B5 administration to Plasmodium berghei infected BALB/c mice. Method: 32 males BALB/c mice were infected by 200 µL blood which contain 106 Plasmodium berghei intraperitoneally. Then, samples were separated randomly into four groups, namely control group, group P1, group P2 and group P3. As soon as parasitemia reached 1 – 5 % the treatment should begin. Control group was administered aquades by gavage, group P1 administered 0.14 g/kgBW provitamin B5, group P2 administered 1.4 g/kgBW provitamin B5, group P3 administered 2.8 g/kgBW provitamin B5, all were treated by gavage. Provitamin B5 treatment followed the protocol in the 4-days suppressive test of blood schizontocidal action. On the fourth day the mice were terminated and blood samples from intracardiac was taken. Thus, blood samples conducted erythrocyte GSH measurement using Anderson method. Result: The results were analysed by using Anova α = 0.05, and continued by LSD if the result showed a significant difference. Erythrocyte GSH level decreased in all groups. Erythrocyte GSH in group P3 increased significant compared to group P1 ( P<0.05). Parasitemia measurement using Percent method showed a significant decrease in group P1 ( 48 % ) and in group P2 ( 62 % ) (P<0.05), while in group P3 no significant difference from control group. Conclusion: Erythrocyte GSH level decreased in administration of Provitamin B5 by increasing dosage, in contrast to parasitemia percentage.